Awareness of hypertension guidelines and the diagnosis and evaluation of hypertension by primary care physicians in Nigeria - Ale, OK (Cardiovasc J Afr, 2017)
BACKGROUND: The availability of numerous hypertension guidelines seems not to have impacted significantly on the burden of hypertension. We evaluated awareness of hypertension guidelines among primary-care physicians (PCPs) in Nigeria and its relationship to hypertension diagnosis and work up. METHODS: Anonymous self-administered questionnaires were filled in by PCPs categorised into two groups: hypertension guideline aware (GA) and unaware (GU). RESULTS: The 403 participating PCPs had a mean age and experience of 40 ± 11.34 and 14 ± 11.10 years, respectively, with 46.7% (n = 188) of them being GA. Out of the 19 questions assessed, GA and GU PCPs performed better in seven and two questions, respectively, while the two subgroups had a similar performance in 10 questions. The performance of the PCPs in government and private practice was similar. CONCLUSIONS: There is a gap between guideline recommendations and hypertension care in Nigeria that is further widened by PCPs’ unawareness of the guidelines. Popularising hypertension guidelines among PCPs may significantly improve hypertension care and reduce the burden of disease.